2008
DOI: 10.1051/dst:2008006
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatment of cream affects the physicochemical properties of sweet buttermilk

Abstract: -The objective of this work was to investigate the effect of heat treatment of sweet creams on the physicochemical properties of sweet industrial buttermilks. Creams with three different heat treatments: low, medium and high, were churned and the corresponding buttermilks were characterised. Furthermore, buttermilks were renneted and centrifuged to obtain insoluble pellets and supernatants. The physicochemical properties such as the particle size measured by laser light scattering and composition of creams, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
4
16
0
1
Order By: Relevance
“…Buttermilk pH, in general, ranges from 6.4 to 6.8 (Sodini et al. 2006,; Gassi et al. 2008), values near to the ones found in milk and in the present study.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Buttermilk pH, in general, ranges from 6.4 to 6.8 (Sodini et al. 2006,; Gassi et al. 2008), values near to the ones found in milk and in the present study.…”
Section: Resultssupporting
confidence: 82%
“…These differences are probably due to the composition of the cream and the processing parameters to manufacture the butter, such as time and temperature of churning, which can differ from one industry to another. Buttermilk pH, in general, ranges from 6.4 to 6.8 (Sodini et al 2006;Gassi et al 2008), values near to the ones found in milk and in the present study.…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 83%
“…Moreover, the impact of different buttermilk processing technologies and enzymatic hydrolysis has not yet been studied. It is known that heat processing of cream modifies the composition and structure of MFGM to a considerable extent [8,24]. Heat treatment denatures whey and MFGM proteins, resulting in the formation of various complexes with caseins [3,5,8,29].…”
Section: Introductionmentioning
confidence: 99%
“…Both cited authors, analogous to our research, obtained buttermilk from sweet cream. According toSodini, Morin, Olabi, and Jiménez-Flores (2006), the use of ether sweet or sour cream for butter production influences the buttermilk composition Gassi et al (2008). pointed out that buttermilk properties depend on origin of milk, heat treatment of cream, and butter technology (slow or rapid churning).…”
mentioning
confidence: 99%